Characterization and partial purification of an ATPase and inorganic pyrophosphatase of the archaebacterium Methanobacterium thermoautotrophicum - Roth, R; Bachofen, R (Biochimica et biophysica acta, 1994)
ATPase and inorganic pyrophosphatase (PPase) activities have been detected in several methanogenic bacteria. These activities are believed to play a crucial role in energy metabolism. In the present study we have investigated some characteristics of the ATPase and the inorganic PPase activities of Methanobacterium thermoautotrophicum. Although these proteins migrate identically on non-dissociating gels, they are catalyzed by distinct enzymes which are separable by biochemical purification methods. The partially purified enzymes are composed of at least two subunits. The ATPase subunits have molecular masses of about 43 and 33 kDa and the inorganic PPase such of about 31 and 25 kDa. After purification, the PPase and the ATPase did not hydrolyze ATP and PP(i), respectively. The membrane-bound ATPase and PPase activities are distinguished in response to sodium fluoride, by the effects of divalent cations, by the temperature ranges for activities and the solubilization behaviour by different extractants. Most investigated catalytic and structural properties of the ATPase do not suit the current criteria for classifying this enzyme under either the F-, V- or P-ATPases.